HYDRO-PHYSICAL CHARACTERISTICS OF SUBSTRATES FOR LETTUCE PRODUCTION IN FLOATING GROWTH SYSTEM - Monteiro, Alex Becker; dos Santos Pereira, Ivan; Luís Bamberg, Adilson; Mariliz Stöcker, Cristiane; Lacerda Ribeiro, Pablo; Carlos Timm, Luís (IRRIGA, 2020)
HYDRO-PHYSICAL CHARACTERISTICS OF SUBSTRATES FOR LETTUCE PRODUCTION IN FLOATING GROWTH SYSTEM ALEX BECKER MONTEIRO1; IVAN DOS SANTOS PEREIRA2; ADILSON LUÍS BAMBERG3; CRISTIANE MARILIZ STÖCKER4; PABLO LACERDA RIBEIRO5 E LUÍS CARLOS TIMM6 1Departamento de Solos, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, alexbeckermonteiro@gmail.com. 2Departamento de Solos, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, ivanspereira@gmail.com. 3Embrapa Clima Temperado, Rodovia BR 392, km 78, 9º Distrito, CEP 96010-971, Pelotas, Rio Grande do Sul, Brasil, adilson.bamberg@embrapa.br. 4Departamento de Fitotecnia, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, crisstocker@yahoo.com.br. 5Departamento de Solos, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, pabloribeirolr@gmail.com. 6Departamento de Engenharia Rural, Universidade Federal de Pelotas, Campus Universitário, s/n, CEP 96160-000, Pelotas, Rio Grande do Sul, Brasil, lctimm@ufpel.edu.br. 1 ABSTRACT The objective was to evaluate the hydro-physical properties of different substrates and their effects on the development of lettuce seedlings in a floating system. The study was carried out in a greenhouse during the months of January and February of 2017. The design was randomized blocks with 16 treatments, represented by 13 proportions of substrates based on organic fertilizer, carbonized rice husk and vermiculite, and three other commercial substrates. The hydro-physical characteristics (granulometric fraction, dry bulk density, total porosity, aeration space, easily available water, available water, remaining water and water retention capacity), pH, and electrical conductivity of the substrates were evaluated. Number of leaves, plant height, root system length, fresh mass of root and shoot and dry mass of root and shoot were evaluated at 25 days after emergence. Aeration space and remaining water are the priority hydro-physical variables that should be evaluated in substrates that will be used in floating systems. The formulations with 33.33% organic fertilizer, 43.33 to 53.33% of carbonized rice husk, and 23.33 to 13.33% vermiculite presented the best performance among the substrates studied for the production of seedlings lettuce in floating systems. Keywords: Lactuca sativa L., carbonized rice husk, organic compost. MONTEIRO, A. B.; PEREIRA, I. S.; BAMBERG, A. L.; STÖCKER, C. M.; RIBEIRO, P. L.; TIMM, L. C. CARACTERÍSTICAS FÍSICO-HÍDRICAS DE SUBSTRATOS PARA A PRODUÇÃO DE MUDAS DE ALFACE EM SISTEMA FLOATING 2 RESUMO O objetivo foi avaliar as propriedades físico-hídricas de diferentes substratos e seus efeitos no desenvolvimento de mudas de alface em sistema floating. O estudo foi realizado em casa de vegetação durante os meses de janeiro e fevereiro de 2017. O delineamento foi de blocos casualizados, com 16 tratamentos, representandos por 13 proporções de substratos à base de composto orgânico, casca de arroz carbonizada e vermiculita e três substratos comerciais. Foram avaliadas as características físico-hídricas (fração granulométrica, densidade seca, porosidade total, espaço de aeração, água facilmente disponível, água disponível, água remanescente e capacidade de retenção de água), pH e condutividade elétrica dos substratos. O número de folhas, altura das plantas, comprimento do sistema radicular, massa fresca de raiz e parte aérea e massa seca de raiz e parte aérea foram avaliados aos 25 dias após a emergência. O espaço de aeração e a água remanescente são as variáveis físico-hídricas aprioritárias que devem ser avaliadas em substratos que serão utilizados em sistema floating. As formulações com 33,33% de composto orgânico, 43,33 a 53,33% de casca de arroz carbonizada, e 23,33 a 13,33% de vermiculita apresentaram os melhores desempenhos entre os substratos estudados para a produção de mudas de alface em sistema floating. Palavras-chave: Lactuca sativa L., casca de arroz carbonizada, composto orgânico.